Clozapine Once-Daily Versus Divided Dosing Regimen: A Cross-sectional Study in Japan. Issue 2 (8th March 2022) - Kitagawa, Kohei; So, Ryuhei; Nomura, Nobuyuki; Tsukahara, Masaru; Misawa, Fuminari; Kodama, Masafumi; Uchida, Hiroyuki; Bies, Robert; Straubinger, Thomas; Banker, Christopher; Mizuno, Yuya; Mimura, Masaru; et al.
Abstract : Supplemental digital content is available in the text. Abstract: Objective: Clozapine is generally recommended to be prescribed in a divided dosing regimen based on its relatively short plasma half-life. However, there has been little evidence to support the superiority of divided dosing of clozapine over once-daily dosing. To our knowledge, there have been no studies examining differences in actual plasma concentrations or adverse effects between the 2 dosing strategies of clozapine. We aimed to compare actual plasma concentrations of clozapine between once-daily and divided dosing regimens, and to examine the relationships of these regimens with psychiatric symptoms and adverse effects of clozapine. Methods: We analyzed data from 108 participants of a previous study conducted in 2 hospitals in Japan. A population pharmacokinetic model was used to estimate the peak and trough plasma concentrations of clozapine based on actual plasma concentrations. We evaluated psychiatric symptoms with the Brief Evaluation of Psychosis Symptom Domains and adverse effects of clozapine with the Glasgow Antipsychotic Side-effects Scale for Clozapine. Results: The estimated peak and trough plasma concentrations of clozapine did not differ significantly between once-daily and divided dosing regimens. There were no significant differences in psychiatric symptoms except for depression/anxiety or subjective adverse effects of clozapine between the 2 dosing strategies. Conclusions: Our findings tentatively support the feasibility and clinical utility of once-daily dosing of clozapine in clinical practice. Further studies are needed to replicate these findings and determine causality between dosing strategies and clinical outcomes.